The Importance of Mastering the Material for Teachers in Student Development - Maharani, Jenny; Damia, Nazla (International Journal of Students Education, 2023)
This research was conducted so that a teacher is required to master the subject matter, because subject matter is a very urgent activity in the teaching and learning process, so teachers mastering the subject matter can broaden the horizons of students’ thinking horizons. Learning is a mental activity that takes place in active interaction with the environment. Learning produces changes in knowledge, skills and attitudes. Learning is the process of interaction between students and educators by using learning resources in a learning environment and producing learning outcomes which can later be assessed by the teacher. The success of learning achievement is greatly influenced by several factors, including teacher factors, student factors, and environmental factors. Teacher factors include, the teacher’s ability not only in mastering the subject matter, but also including the accuracy of choosing strategies, methods and approaches used in learning activities, the low ability of teachers in mastering learning material is the cause of the low quality of learning outcomes, the development of teacher professional competence in implementing learning process, the limited ability of teachers to master this material leads to the low quality of students as graduates who will take part in learning at the next level. The aim of this research is to find out how to improve teachers’ abilities in mastering learning material at school.